In silico design of sitagliptin bioisosteres as new inhibitors of Mpro SARS-CoV-2 - Abelardo Abad-Giron, Lucero Asmad-Cruz, Angella M. Cordova-Muñoz, Cesar D. Gamarra-Sanchez, Carmen R. Silva-Correa, Víctor E. Villarreal-La Torre (Journal of Applied Pharmaceutical Science, 2024)
Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the virus that caused the last major pandemic and has led to multiple efforts being carried out around the world to investigate molecules such as specific chemotherapy drugs against this virus, such as the drug Sitagliptin, which inhibits Mpro, a protease of the virus, by acting on a highly conservative substrate recognition pocket in different coronaviruses. The study aims to develop new compounds under bioisosteric replacement techniques and obtain new SARS-Cov-2 Mpro inhibitors that are more effective than Sitagliptin. For this, 50 bioisosteric derivatives of Sitagliptin were designed, and the pharmacodynamic, pharmacokinetic, and physicochemical properties were analyzed. First, the physicochemical properties of oral absorption were analyzed according to the principles of Lipinski and Veber. The molecular docking was carried out between the protease Mpro (Protein Data Bank Code 7BB2) and the 26 bioisosteres that had the best oral absorption, with the bioisosteres modified in 2,4,5-trifluorophenyl being those that presented a lower affinity energy than that of Sitagliptin. In addition, molecules with pyrrole-pyrazole or similar groups have better pharmacokinetic properties. It is concluded that the pyrrole-pyrazole carboxamide derivative molecule has better energy affinity and ligand efficiency than the other bioisosteres; additionally, it has adequate pharmacokinetic properties, so it would be the best candidate to continue in in vitro or in vivo studies.
Keywords: Sitagliptin, molecular docking, Mpro protein, bioisostere, SARS-CoV-2